ANALYSIS OF ENVIRONMENTAL PERFORMANCE, ENERGY CONSERVATION, AND EMISSION REDUCTION IN THE FINANCIAL PROSPECTIVE - CHOIRUL ANWAR (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
Abstract. This article discusses the effect of environmental disclosure to financial performance (quantitative case study of company listed in Indonesia Stock Exchange in the year 2008). Empirical result of this study furthermore is being extended by qualitative research for exploring more deeply about implementation of green gas houses in Indonesia trough energy audit. The quantitative research in this study is based on cross-sectional empirical applied research. Through a purposive judgment sampling technique, 31 companies listed in Indonesia Stock Exchange which also participated in PROPER (environmental program held by Indonesian Ministry of Environment) were included in this study. The first hypothesis is asserted as there is significant effect between environmental performance and financial performance. The second hypothesis is asserted as there is significant effect between environmental disclosure and financial performance. The method of data analysis is multiple linear regressions. The results for both first and second hypotheses indicated that environmental performance and disclosure were significantly affecting financial performance. Further qualitative study in this article extends empirical result of above study. This study discusses about energy conservation and emission reduction in 16 steel industries and 5 pulp and paper industries. Based on result of audit energy that is converted to economical measurement, this study came up with the conclusion that many industries are still extravagant in consuming energy due to inefficient of old equipment process and lack of energy flow Metter measurement. By showing the comparison results of energy consumption in old and new equipment process that are converted to economical measurement, this study recommends to use new machinery for industrial life cycle to support green gas houses program. Keywords: environmental, energy conversion, emission reduction, financial performance